An assessment of the likely impact on Ugandan households of rising global food prices - Benson, Todd; Mugarura, Samuel; Wanda, Kelly (International Food Policy Research Institute, 2008)
The Uganda offices of WFP, UNICEF, and FAO commissioned the Kampala office of the International Food Policy Research Institute (IFPRI) to assess the likely impact of rising world food prices on the welfare and food security of Ugandan households. This study was done in May 2008 and was based primarily upon secondary information from the Uganda Bureau of Statistics, the Uganda Revenue Authority, and the FoodNet market price information project. The study team also mounted a rapid, qualitative survey of established wholesale food traders in seven markets. Uganda is a significant producer of food within central and east Africa. Traditionally, Uganda has been the most important food exporter in the region, particularly of maize to Kenya. Wheat and rice are the main food imports, coming from global markets. However, the main sources of calories for the population come from crops that are not extensively traded - matooke (cooking banana), cassava, and sweet potato. Almost three-quarters of the consumption of these foods is from the own production of consuming households. As such, at national level, Uganda is food secure. However, over the past 20 years there has been significant localized food insecurity arising from continued political turmoil in northern Uganda linked to the Lord's Resistance Army (LRA), as well as poor harvests and general insecurity in the Karamoja region in the northeast, primarily. These populations are the most vulnerable to food insecurity in the country.